Strukturelle und kulturelle Grundlagen des Politischen in Ostmitteleuropa im 20. Jahrhundert - Puttkamer, Joachim von (Comparativ, 2008)
Structural and Cultural Foundations of the Political Sphere in East Central Europe in the 20th Century The cultural turn in political history challenges established notions of East Central Europe. Yet, a survey of recent studies shows that the concept of East Central Europe is still provides valid insights into specific traits of the regions within a European context. The article explores the national connotations of statehood since the late nineteenth century. It argues that not so much unsolved minority problems, but rather the need to develop coherent ideas of a national state and a national territory within the majority populations posed the most serious problems in establishing the new political order after 1918. The answer was to link national statehood to farreaching reform projects. The communist regimes took a similar approach in propagating socialist utopia within a national framework. Even today, discourses of national statehood, liberty and civil society reflect specific traditions of the historical experience of East Central Europe.